The DSM: mindful science or mindless power? A critical review - Khoury, Bassam; Langer, Ellen J.; Pagnini, Francesco (Frontiers in Psychology, 2014)
In this paper we review the DSM, its scientific bases and utility. The concepts of “normality”, “pathology” and boundaries between them are critically reviewed. We further use the concepts of mindfulness and mindlessness, and evidence from cognitive and social sciences to investigate the DSM clinical and social impact and we argue against its assigned overpower. We recommend including alternative perspectives to the DSM, such as mindfulness and positive psychology. We also argue for including mindfulness training in psychiatric residency and clinical psychology programs.